Implementing a Subnational Results-Oriented Management and Budgeting System : Lessons from Medellín, Colombia - Gómez, Rafael; Olivera, Mauricio; Velasco, Mario A. (Washington, DC: World Bank, 2017)
After a century of political centralization in Colombia, the first public election of city mayors in 19861 began a decentralization trend, which was later reinforced by a constitutional reform in 1991. Subnational governments (departments and municipalities) were made responsible for the planning and management of social and economic development in their jurisdictions. Administrative and political reforms were accompanied by fiscal decentralization, including the transfer of central government revenues. Since 1991 the growth of fiscal transfers has accelerated. Departments and municipalities are now responsible for public health, education, water supply, and sanitation expenditures through earmarked transfers. Out of the total amount of central government expenditures (21.8 percent of GDP (Gross Domestic Product) in 2008) almost one-quarter represent regional transfers (5 percent of GDP), which finance half of all regional expenditures (10.2 percent of GDP). The purpose of this paper is to describe the budget process reform implemented in Medellin, and to analyze its actual performance and evaluate its success. The reform is changing the way public resources are allocated and executed, while gradually institutionalizing supply and demand-side practices beyond the government's political cycles. This paper describes and analyzes how the Results-oriented budgeting (RoB) was designed and implemented, and the achievements of the system to date, in terms of resource allocation and the policy-making process.